A case report of arthrocentesis in temporomandibular joint internal derangement - Thanseeh, Muhammed; Rohith, R; Sreejith, V P; Puthalath, Ushas; Jose Tom, Jibin (Indian Journal of Case Reports, 2024)
In this case report, a 56-year-old male presented to our department of oral and maxillofacial surgery with a chief complaint of pain during mouth opening on the left joint region. The patient also complained of limited mouth opening and temporomandibular joint (TMJ) pain. Arthrocentesis was performed under aseptic conditions. Clinical evaluation of the patients was done before the procedure, 1 week, 1 month, and 4 months postoperatively. Intensity of TMJ pain and maximal mouth opening were recorded at each follow-up visit. There was a significant improvement in mouth opening and a reduction in pain scores in the postoperative period. Arthrocentesis is a simple and safe procedure for patients with internal derangement with a closed lock for improving mouth opening and decreasing pain.